Identification of best Fit Models for Fuelwood Consumption in Foothills of Western Himalayas - Mushtaq, Tahir; Ahmad, Mir Awsaf; Banyal, Rakesh (Indian Forester, 2016)
A survey of household fuelwood consumption was carried out in Samba district of Jammu and Kashmir, India in the year 2011. Different models for fuelwood consumption (social, economic, alternate, biophysical and composite) were prepared to identify best fit models. The households surveyed covered heterogeneous population belonging to different income, educational and social groups. There was more availability and utilization of fuelwood as energy resources in domestic sector as compared to the commercial fuels. Dung cakes, crop residues and fuelwood were found to be the three main fuels used for cooking, though LPG was also used along with biomass fuels. But complete conversion to cleaner fuels has not taken place yet even in households that had been using LPG for many years. Income was an important factor determining the choice of fuel for cooking, but there were some socio-cultural factors which were equally important in making fuel preferences at household level. Based on logistic regression analysis, out of five models (alternate, social, economic, biophysical and composite) only three (social, economic and composite) were valid in predicting fuelwood consumption. Economic and composite models were equally accurate in predicting fuelwood consumption. The composite model implies that the economic factors dominated fuelwood consumption.